2020
DOI: 10.1002/pat.5095
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(l‐lactide) nanofibers coated with mineral trioxide aggregate enhance odontogenic differentiation of dental pulp stem cells

Abstract: A combination of bioceramics and nanofibrous scaffolds holds promising potential for inducing of mineralization in connective tissues. The aim of the present study was to investigate the attachment, proliferation and odontogenic differentiation of dental pulp stem cells (DPSC) on poly(L-lactide) (PLLA) nanofibers coated with mineral trioxide aggregate (MTA). Polymeric scaffolds were fabricated via the electrospinning method and their surface was coated with MTA. DPSC were isolated from dental pulp and their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This data indicated that DPSCs grown on PLCL scaffold could be differentiated into cells showing an osteoblast immunophenotype and secrete a mineralized bone-like matrix. In line with other reports, we might conclude that PLCL nonfibrous scaffold provided a favorable microenvironment for the intracellular signaling activity in cell–cell and cell–extracellular matrix interactions and affected osteogenic differentiation of hDPSCs and mineralization of ECM [ 45 , 46 ]. Based on the presented results, bioconstruct designed of adherent hDPSCs to PLCL nonfibrous scaffold showing high proliferation, osteogenic potency and mineralization ability seems to be a promise graft materials for bone tissue engineering [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This data indicated that DPSCs grown on PLCL scaffold could be differentiated into cells showing an osteoblast immunophenotype and secrete a mineralized bone-like matrix. In line with other reports, we might conclude that PLCL nonfibrous scaffold provided a favorable microenvironment for the intracellular signaling activity in cell–cell and cell–extracellular matrix interactions and affected osteogenic differentiation of hDPSCs and mineralization of ECM [ 45 , 46 ]. Based on the presented results, bioconstruct designed of adherent hDPSCs to PLCL nonfibrous scaffold showing high proliferation, osteogenic potency and mineralization ability seems to be a promise graft materials for bone tissue engineering [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, a pure PLCL scaffold is hydrophobic, and some modifications are needed to improve its physicomechanical properties [ 42 , 44 , 45 ]. Recently, several reports found that the modification of electrospun poly( l -lactide) or poly(ε-caprolactone) nanofiber scaffolds improves hDPSCs osteogenic differentiation [ 5 , 39 , 46 ]. Although electrospun nanofibers scaffolds showed high potential in bone tissue engineering, different problems must be solved.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paradigm shift for endodontic therapy in dentistry from simple capping to dental tissue reconstruction because the effectiveness and durability of the use of specialized tissue-compatible materials in conventional dental therapies is still unclear [49]. Tissue engineering approaches based on cell-based, scaffolds based and scaffold-free cell-based strategies are used to discover the ideal treatment method and material that modulates tissue defence/repair and promotes dentinpulp complex regeneration [50,51].…”
Section: Conventional and Tissue Engineering-based Vital Pulp Treatmentmentioning
confidence: 99%
“…Tissue-engineering approaches appear highly promising for the regeneration of injured tissues [ 158 ]. In dentistry, we are looking forward to the technology that allows for the regeneration of tissues such as the periodontal ligament, enamel, dentin, and alveolar bone [ 159 , 160 ]. Tissue engineering combines three critical components: scaffolds, mesenchymal stem cells (MSCs), and growth factors, and seems to be an auspicious approach in dentistry [ 158 , 161 ].…”
Section: Potential Applications Of Hybrid Multifunctional Nanofibersmentioning
confidence: 99%
“…A scaffold must be designed with appropriate biocompatibility, biodegradability, architecture, and mechanical properties to promote the formation of a natural, extracellular matrix [ 158 , 161 , 162 ]. Recently, hybrid nanofibers, including coated nanofibers, have attracted the attention of investigators since they have shown to promote stem cells’ adhesion, growth, and differentiation into functional cells [ 160 , 161 , 162 ]. However, in vitro and in vivo experimental studies which described the biological effect of the nanofibrous scaffold with loaded MSCs in bone-tissue engineering are limited [ 163 , 164 , 165 ].…”
Section: Potential Applications Of Hybrid Multifunctional Nanofibersmentioning
confidence: 99%